Harmful Cyanobacterial Blooms: Causes, Consequences, and Controls - Paerl, Hans W.; Otten, Timothy G. (Microbial ecology, 2013)
Cyanobacteria are the Earth's oldest oxygenic photoautotrophs and have had major impacts on shaping its biosphere. Their long evolutionary history (∼3.5 by) has enabled them to adapt to geochemical and climatic changes, and more recently anthropogenic modifications of aquatic environments, including nutrient over-enrichment (eutrophication), water diversions, withdrawals, and salinization. Many cyanobacterial genera exhibit optimal growth rates and bloom potentials at relatively high water temperatures; hence global warming plays a key role in their expansion and persistence. Bloom-forming cyanobacterial taxa can be harmful from environmental, organismal, and human health perspectives by outcompeting beneficial phytoplankton, depleting oxygen upon bloom senescence, and producing a variety of toxic secondary metabolites (e.g., cyanotoxins). How environmental factors impact cyanotoxin production is the subject of ongoing research, but nutrient (N, P and trace metals) supply rates, light, temperature, oxidative stressors, interactions with other biota (bacteria, viruses and animal grazers), and most likely, the combined effects of these factors are all involved. Accordingly, strategies aimed at controlling and mitigating harmful blooms have focused on manipulating these dynamic factors. The applicability and feasibility of various controls and management approaches is discussed for natural waters and drinking water supplies. Strategies based on physical, chemical, and biological manipulations of specific factors show promise; however, a key underlying approach that should be considered in almost all instances is nutrient (both N and P) input reductions; which have been shown to effectively reduce cyanobacterial biomass, and therefore limit health risks and frequencies of hypoxic events.